The Dialogue of Heidegger with Pre-Socratic Philosophers - Martín Morillas, Antonio M. (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
The German philosopher Martin Heidegger (1898-1976) attempted to outline in his second philosophy a hermeneutics of the thought of some philosophers (Anaximander, Parmenides and Heracleitus) prior to the metaphysical development of Western thought. In several of his second work’s writings, Heidegger delimits, examines and reinterprets certain primitive Greek notions, which were especially appropriate for the jump from the «first beginning» of philosophy in Greece to the «other beginning» (not a metaphysical one) of a «thinking of being» (Seinsdenken) as «appropriating event» (Er-eignis). They are the pre-Socratic notions of Chreón (necessity), Lógos (thought-word), Móira (fate), Alétheia (truth) y Ph?sis (nature-reality). Within the context of his long ontological research on the «essencing of being» (Seinswesen), Heidegger offers a reading in terms of an overcoming (Überwindung) of metaphysical thought in general, understood as onto-theo-logy and marked by its «forgetfulness of being».